Strategi Promosi dan Store Interior Terhadap Daya Beli Konsumen Pada Industri Ritel (Studi Kasus Indomaret Johor) - Ronda Deli Sianturi; Anda Yanny (Forum Kerjasama Pendidikan Tinggi, 2021)
To increase customer interest in the purchase of a product, companies must jointly maximize appropriately what is needed customer. Promotion is important factor to increase the interest of the customer purchase. Store Interior is also an important factor to increase the interest of customer purchase. Currently the retail industry such as Indomaret Johor has decreased the number of consumers. The purpose of this study was to determine the effect of promotion and interior toward customer purchase interest Indomaret Johor. This type of research is quantitative. Sources of data obtained through field research and library research. The number of samples taken from 25 people Indomaret customers Johor. This study used SPSS V.20 and multiple linear regression. Data analysis techniques used in this research is multiple linear regression analysisto analyze the impact of promotions and store interiors to the interest of customer’s purchase. The analysis showed that the variables of sale and store interior have a significant influence on interest of the customer purchase Indomaret Johor. This show that promotion and store interior as benefit for customers that will affect the buying interest of customers to maka a purchase.This research provides benefits for compaies in order to prioritize in managing the promotion and store interior more effectively because customers prefer promotions and store interior to make a purchase